Predicting hospital length-of-stay outliers using decision tree induction. - Yap, Joanne Geok Lan. (2008)
Two data mining techniques, decision tree induction and rule induction, were applied to casemix and patient data from a Singapore hospital to develop models for predicting hospital length-of-stay outliers.